1998
DOI: 10.1111/j.1699-0463.1998.tb01377.x
|View full text |Cite
|
Sign up to set email alerts
|

A histomorphometric study of haematological disorders with respect to marrow fibrosis and osteosclerosis

Abstract: A retrospective investigation of 75 EDTA‐decalcified Jamshidi biopsies collected over a 2‐year period at Aarhus University Hospital was performed. The biopsies originated from 75 patients suffering from idiopathic myelofibrosis, other chronic myeloproliferative disorders, or other conditions with known associations with bone marrow fibrosis. The relative volumes of trabecular and woven bone, as well as haematopoietic and non‐haematopoietic tissue, were estimated histomorphometrically. The degree of fibrosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…29 The aberrant cellular trafficking in IM has been previously attributed to the disruption of the BM microenvironment, which occurs as a result of reactive BM fibrosis and osteosclerosis. 37 This explanation seems unlikely, however, since allogenic stem cell transplantation of peripheral blood grafts for patients with IM is not characterized by delayed engraftment or a high rate of graft failure. [38][39][40][41] Surprisingly, the rate of graft failure has been reported to be higher following autologous stem cell transplantation than allogenic stem cell transplantation, [38][39][40][41] suggesting that HSC/HPC homing and engraftment are not adversely affected by the BM microenvironment in IM.…”
Section: Discussionmentioning
confidence: 99%
“…29 The aberrant cellular trafficking in IM has been previously attributed to the disruption of the BM microenvironment, which occurs as a result of reactive BM fibrosis and osteosclerosis. 37 This explanation seems unlikely, however, since allogenic stem cell transplantation of peripheral blood grafts for patients with IM is not characterized by delayed engraftment or a high rate of graft failure. [38][39][40][41] Surprisingly, the rate of graft failure has been reported to be higher following autologous stem cell transplantation than allogenic stem cell transplantation, [38][39][40][41] suggesting that HSC/HPC homing and engraftment are not adversely affected by the BM microenvironment in IM.…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometric measurements in a cohort of 75 MPN patients have shown that MF patients have significantly more bone tissue compared with other MPN-type patients, and that there is a positive correlation between the amount of bone and the degree of fibrosis [25]. Bone appositions are due to a thickening of existing trabeculae and not gain of new trabeculae [26].…”
Section: Myelofibrosismentioning
confidence: 99%
“…It is now generally accepted that megakaryocytes play a causal role in myelofibrosis, 31,32 and this in turn is associated with osteosclerosis. 33,34 In addition, increased numbers of megakaryocytes were observed in postmenopausal women receiving high-dose estradiol therapy, 35 mice treated with high-dose estradiol, 36 and rats treated with high-dose 1,25-(OH) 2 vitamin D 3 . 36a Although megakaryocytes produce a number of growth factors such as platelet-derived growth factor (PDGF) or transforming growth factor ␤ (TGF-␤), known to modulate the growth of BMSCs, 26,27,37 it is unlikely that these play a role in the activity described here.…”
Section: Megakaryocyte-bmsc Aggregatesmentioning
confidence: 99%